Congenital (Infantile) Hypertrophic Pyloric Stenosis (IHPS) - AL Hakeem, Basim H; Hanoudi, Basil M; Hanoudi, Basil M; Malik, Hussen (AL-Kindy College Medical Journal, 2006)
Background: Infantile hypertrophic pyloricstenosis affects 0.5 – 3.0 per 1000 live birth and it isthe most common surgical cause of vomiting ininfancy.Objective: To analyze variable peri-natal factorsthat may be involved in the etiology of infantilehypertrophic pyloric stenosis.Methods: Over a two year's period, from January2000 – December 2001, 31 cases of infantilehypertrophic pyloric stenosis were evaluated forvariable peri-natal risk factors in AL-Eskan centralchild teaching hospital for children.Results: The 31 cases studied were 77.4% malesand 48.4% at three weeks of age. And of all cases,51.6% were breast fed with a blood group (O) beingthe predominant in 54.8%.Normal vaginal delivery was in 80.6% of cases. Allinfants 100% had vomiting, and 48.4% of thempresented with Jaundice and only 16.1% hadconstipation. There were no significant correlationsbetween age and pyloric mass size, age and presenceof jaundice or between pyloric mass size and thepresence of jaundice.Conclusion: Infantile hypertrophic pyloric stenosisis a common condition affecting young infants and itsetiology remains unknown, more genetic andenvironmental factors should be investigated in thefuture.